Widefield indocyanine green angiography evaluating choroidal vein drainage pattern and choroidal vein alterations in acute and chronic central serous chorioretinopathy - Xinlei Hao; Guiqin He; Miaoling Li; Jiaxin Pu; Xuenan Zhuang; Yongyue Su; Xiongze Zhang; Feng Wen (Photodiagnosis and Photodynamic Therapy)
Purpose: To access the distribution of choroidal vein drainage pattern and the choroidal vein alterations in choroidal vascular hyperpermeability (CVH) areas in eyes with acute and chronic central serous chorioretinopathy (CSC) using widefield indocyanine green angiography (WF-ICGA). Methods: In this retrospective observational study, medical records and multimodal imaging of 127 patients (165 eyes) with CSC were reviewed. The number and location of dominant vortex veins and CVH areas on WF-ICGA images were evaluated. Choroidal vein alterations, including fusiform, bulbosity, sausaging, choroidal vein confluence and intervortex venous anastomosis, were identified in CVH areas. The differences of choroidal features were compared between acute and chronic groups. Results: Sixty-three acute CSC eyes and 102 chronic CSC eyes were evaluated. In this study, 125 eyes (75.76 %) exhibited an asymmetric pattern of choroidal vein drainage routes. Chronic CSC group had more CVH areas compared with acute CSC eyes in general (P < 0.001). Compared with chronic CSC eyes, CVH areas in acute CSC eyes were more likely to occur in the dominant vortex vein system (P = 0.006). Regarding the choroidal vein alterations, all kinds of anatomical changes were significantly more pronounced in chronic CSC eyes compared with acute group (P < 0.001 for all), with sausaging and intervortex venous anastomosis more commonly observed in chronic group (P < 0.001 and P = 0.002, respectively). The best corrected visual acuity (BCVA) of chronic symmetric CSC was significantly better than that of chronic asymmetric CSC cases (P = 0.006), with the BCVA showing a correlation with the frequency of sausaging dilations (P = 0.032). An increased number of sausaging dilation was associated with poorer visual acuity in chronic asymmetric CSC. Conclusions: Choroidal vascular remodeling occurs throughout the entire course of the CSC, with the formation of intervortex venous anastomosis creating a new drainage path that helps ameliorate choroidal vein congestion over time.